Effects of cultivation, washing, and bleaching conditions on bacterial cellulose fabric production. Issue 6 (March 2019) - Han, Juyeon; Shim, Euijin; Kim, Hye Rim
This study aims to compare different conditions in the three-step (cultivation, washing, and bleaching) production of white bacterial cellulose (BC) fabric to introduce it as a new type of fabric in the textile industry. The BC fabric was evaluated on the basis of its surface morphology and chemical structure. The "production BC" after the cultivation step was cultured using glucose as the carbon source in the Hestrin–Schramm (HS) medium. It was produced with the highest production yield (33.2 ± 6.85%), the highest thickness (0.35 ± 0.09 mm), and the flattest surface (211 nm). The bacteria remaining on "washed BC" after the washing step were washed out using 3% NaOH solution, and the nanoscale network structure maintained its integrity after washing. The white BC fabric after the bleaching step was bleached using 5% H2 O2 solution. The white BC fabric with the highest white index (73.15 ± 1.09%) without a natural yellowish-brown color was produced. In the Fourier transform infrared spectroscopy (FTIR) spectra of the white BC fabric, the peaks of proteins and amino acids derived from the bacteria disappeared, while the cellulose I crystal structure was maintained. Also, X-ray diffraction analysis showed that the crystallinity of the white BC fabric increased compared to that of the control sample, and the highest crystallinity of 80.6% was obtained.